Dampak Kesehatan Akibat Kecanduan Game Online Pada Remaja - Rheananda Rhere Fitrajaya; Islam Pandu Utomo; Lina Handayani (Jurnal Cakrawala Promkes, 2022)
Background: The method used in this study is the PRISMA method. The literature used is in the time span between 2018 to 2021. The data used is obtained from Google Scholar using the keywords are online games, youth, health impacts due to playing online games. Objective: what are the causal factors and health impacts caused by playing online games on teenagers. Methods: The method used in this study is the PRISMA method. The literature used is in the time span between 2018 to 2021. The data used is obtained from Google Scholar using the keywords are online games, youth, health impacts due to playing online games. Results: The results of the articles that have been filtered are 55 articles to be analyzed and reviewed, then re-selected so that they become ten articles that meet the inclusion criteria. Conclusions: Playing online games for too long will have a negative impact on the body such as obesity, eye pain, brain disorders, back pain and joint pain